Finding a pathway to language learning advising through teacher autonomy within an Ignatian pedagogical model in a Mexican private university - Ruiz Guerrero, Leticia A. (2022)
This research project aimed to respond to a need perceived as the self-access laboratory (Sas Lab) at a Jesuit Mexican private university reached a stage of maturity in its growth process. The analysis done of the development of Self-access, particularly in Mexico, for this research project, allows us to put forward that our self-access centre is part of the vanguard in our country, having evolved to the point now where we no longer see these spaces as just resource-filled facilities, but rather “person-centred social learning environments” (Mynard, 2016). For us the aim is to support the development of autonomy in learners, language learning is the vehicle to try to reach that goal. This perceived need meant that we required facilitators who would be better prepared to support the development of learner autonomy in the students visiting the Sas Lab. There was a need to prepare teacher-tutors to no longer just transfer teaching skills from their traditional classroom experience to the self-access environment. This meant having to better define the job of facilitators as Language Learning Advisors (LLAs) who are aptly prepared to deal with the overall care and support of the learner to encourage the development of learner autonomy. The main contribution to knowledge that this project proposed was the design of an intervention that would have the teacher-participants use their own autonomy in working together as a community of practice (CoP) to train themselves as LLAs. This intervention was meant to give teachers an opportunity to experience where they stood in terms of autonomy themselves and with this provide them with an understanding of what it would take to accompany a learner to develop it. Part of this novel design would be to use the Ignatian pedagogical model that promotes experiential contextualized learning that is the basis for the work done in Jesuit institutions, like the one where this research took place, to provide a framework for the intervention. This is a first explicit use of the Ignatian paradigm in an English Language Teaching (ELT) context, and it has yielded very promising results that will hopefully shine a light on the possible future applications of it in this and other fields. The intervention itself was done in stages that allowed participants, researcher and the process to have the necessary time to move organically and grow as needed. The first stage of the intervention tracked in an ethnographic study the experience of teachers in the English language programme as they were invited to take an active role in a change management project. This provided a baseline in terms of the overall understanding of teacher autonomy. The second stage of the study saw the formation of a CoP with volunteering participants who started to work towards training themselves as LLAs via means of their own autonomy. An ethnographic study provided an account of the experience and a case study analysis provided insight into the experience of some of the participants. A third stage of the study gathered the work done by the CoP in using their experience to put forward a professional development pathway that is now being used by the department to train and certify LLAs. The experience of having teachers going through a process of self-discovery and exploration of their own autonomy, to better understand where they stood and then to raise their own awareness from first-hand experience about what it takes to develop autonomy as a learner; was a process that had not been proposed before in language learning advising schemes in 3 Mexico or at an international level. Data gathered via means of an interview model designed to allow participants control over the process was proposed, to be consistent with the search for opportunities to support and develop autonomy that characterized the overall design of the intervention. In a wider stage, our experience in this project has brought us a better understanding of the impact of a training scheme that can allow participant teachers to see what it is like to try to take charge of one’s own learning; and learn what it takes to explore and develop autonomy individually and as part of a community learning together.